PENERAPAN ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN UMKM “MIE AYAM TOKET”DI JEMBER - Lestari, Untung Wredhi; Arief, Ahmad Rizqi; Herawati, Diyah; Qomariah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
ABSTRACT This study analyzes the application of SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats) in increasing sales at "Mie Ayam Toket" MSMEs in Jember. SWOT analysis is an important tool in developing business strategies, which allows MSME owners to identify internal strengths and weaknesses, as well as external opportunities and threats that can affect business operations and growth. In the context of "Toket Chicken Noodles", this study evaluates how internal factors such as product quality and customer service, as well as external factors such as market demand and competition, can be optimized to increase sales. The study also includes other approaches such as B/C Ratio to strengthen effective marketing strategies. It is hoped that the results of the SWOT analysis can provide insight to MSME owners about how to overcome existing challenges and take advantage of possible opportunities to increase sales and business success. The conclusions of this study can be the basis for developing a more effective and innovative marketing strategy for "Mie Ayam Toket" in Jember.